A hairdresser's experience in high life - Potter, Eliza (Book collections on Project MUSE., 2009)
Here is the first fully annotated edition of a landmark in early African American literature, the 1859 autobiography of Eliza Potter, a freeborn black woman who, as a hairdresser, was in a unique position to hear about, receive confidences from, and observe wealthy white women. Xiomara Santamarina provides an insightful introduction to this edition that includes newly discovered information about Potter, discusses the author's strong satirical voice and proud working-class status, and places the narrative in the context of 19th-century literature and history.